An Examination Of The Mechanism For Diversion Under Section 90 In Situations Of Juvenile Delinquency Following Partition (Journal of Pharmaceutical Negative Results, 2023)
The purpose of this research is to eliminate first-time offenders and non-dangerous criminals from the traditional legal system. Since criminal prosecution of children and adolescents stigmatizes them, integrating them into community-based rehabilitation programs reduces the chance of future criminal behavior. Following the prosecution of children and adolescents under section 90, an investigation of the use of a rehabilitation plan as an alternative to pursuing criminal proceedings. In-depth interviews with 40 key informants and 19 members of the focus group, for a total of 59 individuals, to acquire specifics, facts, and information regarding the implementation of the rehabilitation plan. It is a qualitative study focusing on the content of primary and secondary data. The study and research on "an analysis of the use of rehabilitation plans according to special measures instead of prosecuting criminal cases after prosecuting children and youth under section 90" resulted in the crystallization of knowledge regarding the implementation of the treatment and rehabilitation plan for juvenile offenders for the greatest efficiency and benefit. Determine unequivocally whether or not it is advised that young offenders possess an authentic sense of initiative. This will permit precise determination of the direction of the operation in accordance with the rehabilitation therapy plan. And there is a high probability of success in carrying out the strategy.